Impact of Phenolic Constituents and Antioxidant Activities of Acer truncatum Leaves and Flowers upon Different Thermal Treatments - Lingguang YANG; Xinxin LIU; Chuang DENG; Peipei YIN (Shipin gongye ke-ji, 2024)
In order to promote the development and application of Acer truncatum leaves and flowers in the food area, in this study, the dynamic changes of their phenolic composition and antioxidant activity were investigated under steam, microwave, and baking treatments, meanwhile, three time periods were further selected to determine the contents of total phenols and major phenolic compounds, together with the variations of antioxidant abilities of samples before and after the three treatments, and those data were finally analyzed through principal components and correlation analyses. The results showed that baking significantly increased the total phenol content from 75.80±3.54 mg GAE/g to 82.55±2.54~87.78±1.53 mg GAE/g in Acer truncatum leaves (P<0.05), while there was no significant difference of the total phenol content among untreated leaves and flowers and those samples under other treatments. Among phenolic compounds in leaves, gallates including gallic acid, ethyl gallate, and 1,2,3,4,6-penta-O-galloyl-β-d-glucose increased in varying degrees under all three treatments, and 1,2,3,4,6-penta-O-galloyl-β-d-glucose increased 1.88-fold under 15 min baking. Nevertheless, prolong microwave or baking treatment led to the reduction of increasing rate of gallates content. The above change pattern of gallates also existed in flowers, but in a relatively gentle mode. The result of antioxidant assays demonstrated that the oxygen radical absorbance capacity values significantly increased in Acer truncatum leaves and flowers after most treatments, and the highest increase in leaves and flowers were 1.49 and 1.21 times, respectively. Principal components and correlation analysis revealed that the variation of the gallates was significantly correlated with the change of the total phenol content, and different phenolic compounds in leaves and flowers had different degrees of contribution to the overall antioxidant activity. The above results indicated that thermal treatment method and time period all significantly affected the phenolic composition and antioxidant activities of Acer truncatum leaves and flowers (P<0.05). Therefore, a proper selection of treatment condition was vital for the improvement of their biological activity and commodity value. Among which, FM10 (microwave treatment for 10 min) led to the enhancement of antioxidant activity of both leaves and flowers. Above all, the present research provided a theoretical basis for the processing and further study of Acer truncatum leaves and flowers as food resources.